2018
DOI: 10.1080/0142159x.2018.1430354
|View full text |Cite|
|
Sign up to set email alerts
|

Test-enhanced learning in health professions education: A systematic review: BEME Guide No. 48

Abstract: TEL demonstrates robust effects across health professions, learners, TEL formats, and learning outcomes. The effectiveness of TEL extends beyond knowledge assessed by examinations to clinical applications. Educators should include TEL in health professions curricula to enhance recall, retention, and transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 58 publications
0
66
0
6
Order By: Relevance
“…Spaced and repeated test enhanced learning promotes better recall and retention again, compared to long single testing or back‐to‐back consecutive testing . Test enhanced learning, as a standalone pedagogy, has demonstrated robust and consistent enhancement of knowledge recall and retention and transfer of medical information …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spaced and repeated test enhanced learning promotes better recall and retention again, compared to long single testing or back‐to‐back consecutive testing . Test enhanced learning, as a standalone pedagogy, has demonstrated robust and consistent enhancement of knowledge recall and retention and transfer of medical information …”
Section: Introductionmentioning
confidence: 99%
“…28 Educational content that is spaced and repeated over time (spaced distribution) increases the acquisition and retention of knowledge compared to content delivered at a single time-point (mass or bolus distribution). 29,30 In addition to measuring knowledge, the process of 'testing' alters the learning process itself to facilitate knowledge retention and transfer, [31][32][33][34][35] a phenomenon also referred to as 'test enhanced learning'. 35 Spaced and repeated test enhanced learning promotes better recall and retention again, compared to long single testing or back-to-back consecutive testing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show that examinations promote both learning and better retention of information (McLachlan, 2006;Larsen et al, 2008;Wormald et al, 2009;Green et al, 2018). Several authors have shown that being tested is a better way to learn than simply rereading the material (Larsen et al, 2008;Green et al, 2018), as students tend to remember it more effectively, a concept described as the "test effect" (Roediger and Karpicke, 2006a,b;Larsen et al, 2008). In addition, meaningful feedback on the assessment enhances student learning and achievements (Fowell et al, 1999;Larsen et al, 2008;Zhang and Henderson, 2015).…”
Section: Introductionmentioning
confidence: 99%